2009
DOI: 10.1021/ja9025243
|View full text |Cite
|
Sign up to set email alerts
|

Water Overcomes Methyl Group Directing Effects in Epoxide-Opening Cascades

Abstract: Water is an effective promoter of the endo-selective opening of trisubstituted epoxides, enabling related cascades leading to a variety of substituted ladder polyether structures. When used in conjunction with a tetrahydropyran-templated nucleophile, water can overcome the powerful electronic directing effect of a methyl substituent at either site of the epoxide, making water a uniquely versatile medium and promoter for epoxide opening.In 1985 Nakanishi advanced a concise and appealing proposal for the biosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 12 publications
1
36
0
1
Order By: Relevance
“…Extending this work further, the Jamison group demonstrated that methyl substituents on epoxides are also tolerated in aqueous cascades (Scheme 15.21b) [201,202]. Under aqueous conditions, diepoxides 279 and 280, which incorporate methyl substituents at the positions of endo attack afforded the triads 282 and 283 (Scheme 15.21b).…”
Section: Epoxide-opening Cascades In the Synthesis Of Polycyclicmentioning
confidence: 98%
See 2 more Smart Citations
“…Extending this work further, the Jamison group demonstrated that methyl substituents on epoxides are also tolerated in aqueous cascades (Scheme 15.21b) [201,202]. Under aqueous conditions, diepoxides 279 and 280, which incorporate methyl substituents at the positions of endo attack afforded the triads 282 and 283 (Scheme 15.21b).…”
Section: Epoxide-opening Cascades In the Synthesis Of Polycyclicmentioning
confidence: 98%
“…A methyl group on a trisubstituted epoxide can be situated in a position where its directing effect promotes endo-opening under acidic conditions (as in 273, Scheme 15.21a) or in a position that would normally promote exo-selective epoxide opening under the same conditions (as in 274, Scheme 15.21a). To incorporate methyl substituents at the ring junctions of the final products in epoxide-opening cascades, the Jamison group, in an immediate extension of their work on aqueous directing group-free endo-selective epoxide openings, prepared and evaluated cyclization reactions of templated epoxy alcohols 273 and 274, which feature both types of methyl substitution on the epoxide (Scheme 15.21a) [201,202]. Acid-catalyzed cyclizations of epoxy alcohol 273 proceeded with high endo selectivity due to the electronic effect of the methyl substituent at the endo site of attack on the epoxide.…”
Section: Epoxide-opening Cascades In the Synthesis Of Polycyclicmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinetic preference for epoxide-opening cascades lies in favor of the exo products, instead of the endo moieties of the ladder poly cyclic ethers 39 . Directing epoxide-opening cascades toward the endo products in the laboratory is made more complex by the inclusion of methyl groups at the ring junctions-seen in every member of the family 40 . This contra-Baldwin challenge, as well as the complex structures and biological activities of this class of polyethers, has enticed many to develop general methods for their preparation 11,39 .…”
Section: Overturning Chemical 'Rules'mentioning
confidence: 99%
“…5 Templating 6 allows for highly-selective THP formation without the need for directing groups, and we have reported the use of a preformed THP 7 or 1,3 dioxane 8 in water-promoted cyclizations. This approach has enabled the synthesis of THPs bearing methyl substituents at the ring junctions 9 as well as marine ladder polyether fragments via polyepoxide cascades. 7b …”
mentioning
confidence: 99%